2021
DOI: 10.3390/pathophysiology28020017
|View full text |Cite
|
Sign up to set email alerts
|

Saponins in Cancer Treatment: Current Progress and Future Prospects

Abstract: Saponins are steroidal or triterpenoid glycoside that is distinguished by the soap-forming nature. Different saponins have been characterized and purified and are gaining attention in cancer chemotherapy. Saponins possess high structural diversity, which is linked to the anticancer activities. Several studies have reported the role of saponins in cancer and the mechanism of actions, including cell-cycle arrest, antioxidant activity, cellular invasion inhibition, induction of apoptosis and autophagy. Despite th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 165 publications
(181 reference statements)
2
63
0
Order By: Relevance
“…Berberine has been reported to inhibit cancer cell growth and metastasis, and exhibit anti-inflammatory properties (Wang et al, 2020). Similarly, baicalin (Verma et al, 2021) and saponin (Elekofehinti et al, 2021) are also reported to be involved in multiple processes of cancer cells, including cell growth and metastasis. The underlying mechanism is not well-identified how a single molecule such as berberine, baicalin, or saponin could affect such many biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine has been reported to inhibit cancer cell growth and metastasis, and exhibit anti-inflammatory properties (Wang et al, 2020). Similarly, baicalin (Verma et al, 2021) and saponin (Elekofehinti et al, 2021) are also reported to be involved in multiple processes of cancer cells, including cell growth and metastasis. The underlying mechanism is not well-identified how a single molecule such as berberine, baicalin, or saponin could affect such many biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Many anticancer mechanisms of these compounds have been reported. They were found to have chemopreventive, cytotoxic, and antimetastatic activities and play a key role in multidrug-resistant cancers ( Elekofahinti et al, 2021 ). In chemoprevention, saponins acted as anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…Among these compounds, alkaloids are very well known as anticancer agents. Furthermore, some of the rest compounds were reported about anticancer activities, for example, rutin, quercetin, and some of their biotransformed metabolites ( Cipák et al, 2003 ; Araújo et al, 2013 ), tannins ( Rajasekar et al, 2021 ; Tikoo et al, 2011 ; AlMalki et al, 2021 ; Youness et al, 2021 ), saponins ( Elekofahinti et al, 2021 ), and quinones ( Kuete et al, 2016 ; Shen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers around the globe have confirmed that saponins isolated from members of the Fabaceae family are effective against colon cancer, melanoma cells, and cervical cancer. Saponins can follow various mechanisms to suppress the progression of cancer by cell cycle arrest, the inhibition of cellular invasion, anti-oxidant activity, and the induction of autophagy and apoptosis [149]. Rochfort and Panozzo [150] stated that the intake of legume saponins enhances the immunity against various types of cancer including cervical and colon cancer.…”
Section: Saponinsmentioning
confidence: 99%